Tourism Security in the Age of Overtourism: A Qualitative Investigation in Bali - Pradnyana, I Putu Hadi (Universitas Pancasakti, 2025)
This research investigates the intricate dynamics of tourism security in Bali, particularly in the context of overtourism, which has led to significant socio-economic and security challenges. Utilizing a qualitative approach, the study engages with various stakeholders, including local residents, tourism authorities, law enforcement, and community leaders, to explore their perceptions and experiences related to tourism security. Data is collected through semi-structured interviews, allowing for an in-depth understanding of the complexities surrounding security risks in high-density tourist areas such as Kuta, Canggu, Petitenget, Kerobokan, and Seminyak. The findings reveal a notable increase in specific types of crime, including theft and scams, exacerbated by the influx of tourists, which has strained local resources and heightened tensions within communities. The research further examines the impact of overtourism on traffic safety, highlighting the challenges posed by increased vehicle volume and inadequate infrastructure. Local authorities have implemented various measures, such as improved traffic management systems and community engagement initiatives, to address these issues. Additionally, the study identifies the role of international travel advisories and perceptions of safety in influencing tourism demand, which in turn affects local security policies. Despite the collaborative efforts among stakeholders, significant barriers remain, including communication gaps and resource limitations, which hinder the effectiveness of tourism security policies. The study underscores the necessity for a more integrated approach that incorporates community perspectives and sustainable practices into tourism security frameworks. By addressing these gaps, the research aims to contribute to the development of effective strategies that enhance the safety and well-being of both tourists and local communities in Bali. Ultimately, this study highlights the importance of understanding the socio-economic dynamics of tourism security in fostering a resilient and sustainable tourism environment in the face of overtourism. The limitation of this study is its qualitative focus, which may not fully capture broader security trends. It also centers on high-density areas, overlooking emerging destinations. Future research could use mixed methods and comparative analyses to enhance understanding and policy effectiveness